Institutional Fragmentation and Metropolitan Coordination in Latin American Cities What Consequences for Productivity and Growth? - Duque, Juan C. (World Bank E-Library Archive, 2019)
This paper provides empirical evidence on the impact of institutional fragmentation and metropolitan coordination on urban productivity in Latin American cities. The use of night-time lights satellite imagery and high-resolution population data allow the use of a broader definition of metropolitan area. Thus, metropolitan area consists of the urban extent that results from the union between the formally defined metropolitan area and the contiguous patches of urbanized areas with more that 500,000 inhabitants. The initial results suggest that the presence of multiple local governments within metropolitan areas generates opposite effects on urban productivity. On the one hand, smaller governments tend to be more responsive and efficient, which increases productivity. But, on the other hand, multiple local governments face coordination costs that reduce productivity